Exploring the development of higher order thinking skills at elementary school - Κούρτης Παρασκευάς; Ντρενογιάννη Ελένη (Education Sciences, 2025)
Within the framework of the revised taxonomy of educational objectives created by Anderson and Krathwohl, this study attempted to describe the design and examine the learning outcomes of an intervention focused at the development of higher order thinking at an elementary education setting. A class of 21 sixth graders participated in the project, which had a duration of 10 months and followed a mixed methods research design. For the needs of the intervention 23 lessons and assignment tasks were designed and implemented. The analysis of the data collected illustrated that overall, students’ performance on higher order thinking tasks has improved.